Increased incidence of thyroid cancer among breast cancer survivors: an analysis of the SEER-9 database (1973–2011). (February 2016) - Kuo, Jennifer H; Chabot, John A; Lee, James A
Aims: We sought to re-examine the incidence of thyroid cancer among breast cancer survivors by performing a population-based, cohort analysis using the SEER-9 database.Methods: We identified 704, 370 breast cancer patients, 49, 663 thyroid cancer patients and 1526 patients who developed thyroid cancer after breast cancer (B1T).Results: Risk for developing thyroid cancer is greatest among survivors diagnosed with breast cancer at age less than 50 years. In general, B1T patients are younger with smaller tumors, and have a greater percentage of invasive ductal carcinoma. They develop thyroid cancer at an older age, and have a greater percentage of aggressive subtypes.Conclusion: Recognition of this association between thyroid and breast cancer should prompt increased awareness in these cancer patient populations.